2023
DOI: 10.3389/fphar.2023.1095721
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid ameliorates dextran sulfate sodium-induced ulcerative colitis in mice via inhibiting NLRP3 inflammasome

Abstract: Background: Ulcerative colitis (UC) is a chronic recurrent inflammatory bowel disease (IBD). The conventional drugs for UC may induce severe side effects. Herbal medicine is considered as a complementary and alternative choice for UC.Purpose: This study aims to estimate the effect of natural polyphenol gallic acid (GA) on the NLRP3 inflammasome with dextran sulfate sodium (DSS)-induced colitis in mice.Study design: The body weights and symptoms of BALB/c mice were recorded. Histological evaluation, ELISA, q-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 42 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…The benefits of G. biloba and its preparations in the prevention and treatment of cardiovascular diseases mainly derive from the effective chemical components such as flavonoids and terpenoid lactones. In this study, through data mining and network pharmacology analysis of relevant literature, we found that the organic acid components (protocatechuic acid, caffeic acid, chlorogenic acid, and gallic acid), flavonoid components (quercetin‐3‐O‐glucoside, quercetin‐3‐O‐rutinoside, kaempferol‐3‐O‐rutinoside, kaempferol‐3‐O‐glucoside, isorhamnetin‐3‐O‐rutinoside, isorhamnetin‐3‐O‐glucoside, apigenin‐7‐O‐glucoside, and apigenin), and terpenoid lactones (bilobalide, ginkgolide A, ginkgolide B, ginkgolide C, and ginkgolide J) had different effects such as anti‐inflammatory and anti‐oxidative activities, protecting the nervous system, changing blood rheology, and so on 22–50 . These components may be the potential active substance basis of its anti‐IS effect, so they were included in the scope of analysis and investigation of the active components of GBE against IS.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The benefits of G. biloba and its preparations in the prevention and treatment of cardiovascular diseases mainly derive from the effective chemical components such as flavonoids and terpenoid lactones. In this study, through data mining and network pharmacology analysis of relevant literature, we found that the organic acid components (protocatechuic acid, caffeic acid, chlorogenic acid, and gallic acid), flavonoid components (quercetin‐3‐O‐glucoside, quercetin‐3‐O‐rutinoside, kaempferol‐3‐O‐rutinoside, kaempferol‐3‐O‐glucoside, isorhamnetin‐3‐O‐rutinoside, isorhamnetin‐3‐O‐glucoside, apigenin‐7‐O‐glucoside, and apigenin), and terpenoid lactones (bilobalide, ginkgolide A, ginkgolide B, ginkgolide C, and ginkgolide J) had different effects such as anti‐inflammatory and anti‐oxidative activities, protecting the nervous system, changing blood rheology, and so on 22–50 . These components may be the potential active substance basis of its anti‐IS effect, so they were included in the scope of analysis and investigation of the active components of GBE against IS.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have shown that ingredients such as caffeic acid, protocatechuic acid, gallic acid, bilobalide, and ginkgolide A can inhibit the TLR4/NF-κB signalling pathway, reduce the expression level of MAPK, and achieve anti-inflammatory effects. 23,25,29,31,33 Bilobalide, ginkgolide A, and so on can play an antiinflammatory role by regulating inflammation-related pathways and inhibiting the release of inflammatory factors. Quercetin-3-O-rutinoside, kaempferol-3-O-rutinoside, kaempferol-3-O-glucoside, and isorhamnetin-3-O-rutinoside can inhibit the PI3K-Akt, NF-κB, and other signalling pathways and reduce cardiovascular and cerebrovascular injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 However, macrophage overactivation can also lead to acute and chronic inflammatory diseases, such as neuroinflammation, neurodegenerative disease, inflammatory bowel disease, pneumonia, and pulmonary fibrosis. [21][22][23][24] Cognitive decline, confusion, impaired motor abilities, tremors, sensory changes, ataxia, and seizures are symptoms of neuroinflammatory and neurovegetative diseases such as stroke, Parkinson's disease, Alzheimer's disease, multiple sclerosis, and epilepsy. [25][26][27] The adverse responses to cyclizine are similar to such symptoms, which are induced by macrophage activation.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are a type of leukocyte that play a critical role in homeostasis and disease prevention by defending the body against invading pathogens 19,20 . However, macrophage overactivation can also lead to acute and chronic inflammatory diseases, such as neuroinflammation, neurodegenerative disease, inflammatory bowel disease, pneumonia, and pulmonary fibrosis 21–24 . Cognitive decline, confusion, impaired motor abilities, tremors, sensory changes, ataxia, and seizures are symptoms of neuroinflammatory and neurovegetative diseases such as stroke, Parkinson's disease, Alzheimer's disease, multiple sclerosis, and epilepsy 25–27 .…”
Section: Discussionmentioning
confidence: 99%